Magnetic and resonance properties of multilayer (Gd/Si/Co/Si)ₙ films - Patrin, G.S.; Vas’kovskii, O.V.; Velikanov, D.A.; Svalov, A.V.; Volkov, N.V.; Eremin, E.V.; Panova, M.A. (Functional Materials, 2004)
Presented are the experimental investigation results of magnetic static and resonance properties of multilayer magnetic films in the system of 4f-3d elements separated by a semiconductor interlayer. Effects of temperature and magnetic field on interlayer coupling are detected. The role of the biquadratic exchange in formation of magnetic state in the whole system is established.